Europeizacja Konstytucji RP na tle rozwiązań państw członkowskich Unii Europejskiej - Kuczma, Paweł (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
The Constitution of the Republic of Poland turned out to be such a universal legal Act, adapted to the changing legal reality, that after joining the EU, Poland only once faced the need to adapt its content to the normative solutions in force in the European Union. The Constitution may be further Europeanised in the future. The Constitution of the Republic of Poland is not completely indifferent to European law; references to international law can be found and its Europeanisation is now taking place indirectly. The subject of consideration in the present article will be to determine the meaning of the term “Europeanisation” as well as to discuss whether the Constitution of the Republic of Poland is a “European” constitution, especially in comparison with the “European” solutions present in fundamental laws of other member states, and whether the state of Europeanisation of the Constitution of the Republic of Poland can be considered satisfactory.
Keywords: constitution; European law; Europeanisation; European integration